Tumbuhan Obat Suku Batak Simalungun dari Cagar Alam Dolok Tinggi Raja - HASIBUAN, IRMAYANI; CHIKMAWATI , TATIK; WALUYO, EKO BAROTO (Jurnal Sumberdaya Hayati, 2016)
Batak Simalungun tribe that inhabited the area around the nature reserve Dolok Tinggi Raja uses many plants species for medicine. This study aimed to examine the use of medicinal plants by the people of Batak Simalungun tribe and determine local knowledge of the tribe in maintaining the sustainability of the medicinal plants in nature. Data obtained from the open and semi-structural interviews, plant exploration, and identification. Batak Simalungun tribe uses 63 species of medicinal plants belonged to 52 genera and 36 families. The herb is used to treat many health problem, such as: hingh and muscles problem, respiratory diseases, digestive diseases, internal disease, skin diseases, nerves, malaria, measles, fever, colds, sore eyes. The herb is also used for increasing stamina and endurance. Medicinal plants used in various ways include direct consumption, mashing, squeezing, extracted, soaked in warm water, steamed, boiled, baked, and fried. The community used various plant parts such as the root, stems, water in stem , bark extract, sap, young leaves, leaves, fruit, or whole parts of the plant, and the most part used is leaves.